Sustainable development goal 2: exploring Bandura’s Triadic Model for behavioural change among urban primary school students - Siow, May Ling; Ramachandran, Sridar; Mohd Tahir, Osman; Shuib, Ahmad (Universiti Malaysia Sarawak, 2023)
The average Malaysian disposes of 15,000 tonnes of food waste per day, out of which 6,000 tonnes is avoidable waste that could feed the poor. This study aims to address food security issues (SDG 2) in Malaysia by using Bandura’s Triadic Model of Reciprocal Determination to examine food wastage behaviours among urban post-millennials. Food waste, which comprises spoilage, preparation waste, and plate waste, is common in schools; as such, qualitative interviews were conducted with 25 urban primary school students in Klang Valley, Malaysia. The findings revealed the interplay between students' personal factors, physical environment factors, and social environment factors in influencing their food wastage behaviours and perspectives. Additionally, it was observed that behavioural changes towards zero-food waste within the school community require environmental interventions, as urban school-goers lack knowledge of food storage alternatives, while their surrounding environment does not support broader food security concerns. Based on the findings, this study proposed a modified triadic model which incorporates permaculture as a sustainable practice in urban schools in Malaysia. Permaculture can act as an environmental stimulus that cultivates students’ positive personal attitudes and feelings towards reducing food waste. Subsequently, there would be a reduction in food waste behaviour within the students' existing ecosystem. This study promotes the reduction of food waste in urban schools and contributes towards formulating a framework for food security in schools.